FAILURES DETECTION METHODOLOGY IN NON RECOVERY COMPUTER SYSTEMS BASED ON DIVERSITY MODELING - Popov, George (International Journal of Computing, 2014)
Diversity is a known approach for increasing reliability of computer systems. The goal of this work is to present quantitative criteria for measure of diversity in non recovery computer systems. For this purpose, the model of diversity-based system with two failure types: detectable and undetectable is presented and a formula to calculate it is proposed.